Combination of Reaction and Separation in Heterogeneous Catalytic Hydrogenation of Ethylformate. Issue 5 (7th April 2015) - Martin, Gerson; Pereira, Carla; Pettersson, Frank; Saxén, Henrik; Murzin, Dmitry Y.; Rodrigues, Alírio; Salmi, Tapio
Abstract Continuous hydrogenation reaction of ethyl benzoylformate was studied over a (–)‐cinchonidine (CD)‐modified Pt/Al2O3 catalyst. The catalyst showed a good stability, and high enantioselectivity was achieved in the fixed‐bed reactor. Chromatographic separation of (R)‐ and (S)‐ethyl mandelate originating from a post‐continuous hydrogenation reaction of ethyl benzoylformate over the (–)‐CD‐modified Pt/Al2O3 catalyst was investigated in the same reaction mixture. A commercial column filled with a chiral selector resin was chosen as a perspective preparative‐scale adsorbent. Since adsorption equilibrium isotherms were linear within the entire investigated range of concentrations, they were determined by pulse experiments for the isomers present in a post‐reaction mixture. Breakthrough curves were measured and described successfully by the dispersive plug‐flow model with linear driving force approximation.